2001
DOI: 10.1093/tropej/47.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Growth Parameters and Endocrine Function in Relation to Echocardiographic Parameters in Children with Ventricular Septal Defect without Heart Failure

Abstract: To determine the effect of ventricular function, size of ventricular septal defect (VSD), and endocrine function on linear growth in children with VSD, we studied 88 children with VSD over a period of 1 year. Growth was assessed by determining the height standard deviation scores (HtSDS) and growth velocity (GV) every 4 months. Two hundred age-matched normal children served as controls for the growth data. Endocrine evaluation was performed in 30 randomly selected children with VSD, and 20 age-matched children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…When we compare the other laboratory parameters; leptin, IGF-1 and IGFBP-3 levels were significantly low in the patient group at initial compared to control. Similar to our results, Soliman et al (28) found that basal IGF-1 levels in patients with VSD were statistically significantly lower than in the control. In the study conducted by Surmeli-Onay et al (29), IGF-1 and IGFBP-3 levels were found to be lower in the in patients with preoperative CHD group compared to the control.…”
Section: Hormonal Evaluationsupporting
confidence: 92%
“…When we compare the other laboratory parameters; leptin, IGF-1 and IGFBP-3 levels were significantly low in the patient group at initial compared to control. Similar to our results, Soliman et al (28) found that basal IGF-1 levels in patients with VSD were statistically significantly lower than in the control. In the study conducted by Surmeli-Onay et al (29), IGF-1 and IGFBP-3 levels were found to be lower in the in patients with preoperative CHD group compared to the control.…”
Section: Hormonal Evaluationsupporting
confidence: 92%
“…Certain studies have demonstrated that the main role of ghrelin in cardiac myocytes is to promote the expression of non-functional GHSR ( 31 ). Another report also indicated that, in addition to GHSR, ghrelin may have other unknown receptors in the cardiac repair system ( 32 ). According to the results of RT-PCR and western blot analysis, ghrelin promoted the expression of GHSR and GH, and repaired hypoxic cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Studies have reported associations of impaired haemodynamic status with impaired growth and with lower body mass index (BMI). 5 6 On the other hand, as the incidence of overweight and obesity increases in the general population, 7 a similar and potentially more pronounced trend might be expected of the CHD population. This may be exacerbated in the CHD population because of potential exercise intolerance and recommendations of activity restriction.…”
Section: Introductionmentioning
confidence: 85%